PEMANFAATAN PEKARANGAN DENGAN TANAMAN BAWANG DAYAK (Eleutherine falmifolia Merr) DI DESA SUNGAI BESAR KECAMATAN KARANG INTAN KABUPATEN BANJAR - Zulipah Mahdalena; Sayidah Nafisa (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This community service activity uses a persuasive approach to identify problems. Find out what the comunity needs and expects in P2M activities for studens at the Faculty of Agriculture Achmad Yani University Banjarmasin. Activity stages include location survey, activity impementation and evaluation. Comunity service activity will be held on 20 -23 September 2024, at the office hall of The Sungai Besar villige sub district, Karang Intan Sub district. The Results of community service activities namely providing information on the benafids of gardens with Dayak Onions plants, have had a positive impact on the comunity, namely by increasing people’s knowledge and insight about cultivation and benefits of Dayak Onions as aTraditional medicine that can help cure various diseases. The People of Sungai Besar Village welcomed and really appreciated all P2M activities